Community mediation in Malaysia: a step forward - Khan, Hanna Ambaras; Abdul Hak, Nora (LexisNexis, 2014)
The Malaysian Department of National Unity and Integration is given hugeresponsibilities to promote unity and to maintain harmony in the country.Simultaneously, the department is given the mandate to initiate a programme that is beneficial towards achieving the above mission. Rukun Tetangga(Peaceful Neighbourhood)Community Mediation is one of the programmes that wasinitiated as a pilot project five years ago. Basically, the programme is a mixture of Rukun Tetangga and Community Mediation to provide skills for the Rukun Tetangga Committee. The purpose of this paper is to study the nature of community mediation under Rukun Tetangga and the professional community mediation and to give suggestions and recommendations on promoting Malaysian Community Mediation, so that the practice of community mediation in Malaysia will achieve an international standard.